Challenges for Autonomous Vehicles (AVs) Engineering: Safety Validation of Functional Performance Limitations. Issue 4 (10th January 2020) - Koné, Tchoya Florence; Bonjour, Eric; Levrat, Eric; Mayer, Frédérique; Géronimi, Stéphane
ABSTRACT: AVs engineering cannot limit itself to the classical safety validation issue, which ensures the vehicle's functional safety. It faces a new safety validation challenge, in the functional performace guarantee of these new vehicle types. This paper presents some validation issue reflections and concludes with some important questions.